Numerical simulations of bistable flows in precessing spheroidal shells. Issue 2 (23rd January 2018) - Vormann, J; Hansen, U
Summary: Precession of the rotation axis is an often neglected mechanical driving mechanism for flows in planetary interiors, through viscous coupling at the boundaries and topographic forcing in non-spherical geometries. We investigate precession-driven flows in spheroidal shells over a wide range of parameters and test the results against theoretical predictions. For Ekman numbers down to 8.0 × 10 −7, we see a good accordance with the work of Busse, who assumed the precession-driven flow to be dominated by a rigid rotation component that is tilted to the main rotation axis. The velocity fields show localized small-scale structures for lower Ekman numbers and clear signals of inertial waves for some parameters. For the case of moderate viscosity and strong deformation, we report the realization of multiple solutions at the same parameter combination, depending on the initial condition.